Annexins: Key Regulators of Haemostasis, Thrombosis, and Apoptosis - Reutelingsperger, Chris P. M. (Thrombosis and Haemostasis, 2001)
Annexins form a family of proteins on the basis of structural and functional criteria. Their physiological relevance is still not fully understood, but is thought to involve phospholipid membrane associated processes. Recent data shed clues about their function in the regulation of thrombosis, haemostasis and apoptosis. These data arise from a multitude of physicochemical, cell biological, animal and clinical studies. This review presents this data and discusses them in the light of the novel understanding that apoptotic cells can contribute to thrombotic and haemostatic processes.
Keywords: Annexins; thrombosis; haemostasis; membrane phospholipids; apoptosis